The Potential of Ustadzah in Improving the Existence of Madrasah Ibtidaiyah Ma'arif Sanggulan Tabanan, Bali - Suharsono Suharsono; Jumari Jumari (Al-Hayat: Journal of Islamic Education, 2020)
One of the factors that play a role in the success of Madrasahs is the potential for female teachers, considering that the teacher profession is very much in demand by women. And the research locus that will be researched by the author, the majority of the teachers are women. Based on this background, the following problems can be raised: 1) The potential of female teachers in improving the existence of MI Ma'arifTabanan Bali for the 2020 academic year? and 2) What are the constraints and solutions for the coaching program for female teachers at MI Ma'arifTabanan? This study uses a qualitative research method, which by definition is a research procedure that produces descriptive data in the form of written words or words from people or observable sources. Sources of data or words in this study were obtained by the author through interviews with people who can be trusted. In this study the authors collected data through several informants including: 1. Head of Madrasah. 2. Management of the Ma'arif Education Institute. 3. Teachers. 4. Employees. 5. Madrasah Committee. Based on the explanation of the results of the research and discussion by the author, it can be concluded that female teachers have the potential to improve the existence of Madrasah IbtidaiyahSanggulanTabanan for the 2020 Academic Year. This is in accordance with the theoretical study which states that potential is an ability that has various possibilities or hopes for further development, either in the form of strength, power, or ability that is obtained by the community directly or through a long process.